[(Z)-O-Ethyl N-phenylthiocarbamato-κS](tricyclohexylphosphine-κP)gold(I): a monoclinic polymorph - Tadbuppa, Primjira P. (International Union of Crystallography, 2010)
The title compound, [Au(C(9)H(10)NOS)(C(18)H(33)P)], represents a monoclinic polymorph to complement a previously reported triclinic (P [Image: see text]) polymorph [Hall et al. (1993 ▶). Aust. J. Chem. 46, 561–570 (unit-cell data only)]. The Au(I) atom is coordinated within an S,P-donor set that defines a slightly distorted linear geometry [S—Au—P = = 175.43 (3)°], with the distortion due in part to a close intramolecular Au⋯O contact [3.036 (2) Å]. In the crystal structure, molecules are arranged into supramolecular chains along the b axis mediated by C—H⋯π interactions.